Quality control of cosmetics containing Calendula officinalis, Melampodium divaricatum, Matricaria chamomila linné and Acchilea millefolium extracts - Isaac, Vera Lucia Borges [UNESP]; Kapp, Camila [UNESP]; Olhe, Camila Arnaldo [UNESP]; Chiari, Bruna Galdorfini [UNESP]; Moreira, Raquel Regina Duarte [UNESP]; Santos, André Gonzaga dos [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Corrêa, Marcos Antônio [UNESP] (My University, 2013)
The use of medicinal plants occurs since the Antiquity, but has become more popular in the present time. In the United States, 50% of the population uses the phytotherapy. Calendula officinalis and Melampodium divaricatum have components called flavonoids. Matricaria chamomila Linn and Acchilea millefolium, popularly known as camomila and mil folhas, respectively, have sesquiterpenic components called azulens. These substances present many effects; some of them offer benefits to the human health. Thus, these plants had their extract incorporated in cosmetic-dermatological formulations. This study aimed to prove the presence of the active substances, sesquiterpenes and flavonoids, in cosmetic creams with Matricaria chamomila Linn, Acchilea millefolium, Calendula officinalis and Melampodium divaricatum extracts. Also, aimed to evaluate the microbiological quality of the products. Flavonoids and sesquiterpernes were detected in the emulsions and the microbiological quality was verified. Thus, the products are safe to the users in relation to the microbiological aspects and should present beneficial effects due to the presence of flavonoids and sesquiterpenes.
Keywords: Plant extracts; Thin layer chromatography; Microbiological control